The Analysis of Noun Derived from Adjective Found in Barack Obama’s Speech and the Teaching of Grammar - Tampangella, Terra; Rokhayati, Titi (JOLLT Journal of Languages and Language Teaching, 2021)
The study is qualitative research. This research deals with noun derived from adjectiveÂ found in Barack Obamaâ€™s speech. The objectives of the research are to find out the position of the noun derived from adjectives in the sentence patternÂ found in Barack Obamaâ€™s speech and to describe the application of noun derived from adjective to teach grammar. In collecting the data, the researchers read the script, identified noun derived from adjectives, analysed the data related to the theory of noun derived from the adjective, analyzing the data quantitatively and qualitatively, applied the finding to teach the grammar at eleventh grade student of Senior High School. The result shows that there are three positions of the noun derived from adjectives based on sentence pattern. They are 30 SVO (Subject + Verb + Object) (50%), 18 SVA ( Subject + Verb + Adverb ) (30%), 12 SVC ( Subject + Verb + Complement ) (20%). The teacher could apply in pre teaching by giving description of Barrack Obamaâ€™s characters, whilst teaching by giving the explanation about part of speech Â and post teaching by strengthening the use of noun derived from adjective as one of part of speech in which it becomes the most important piece in a sentence.